ANALISIS AKUNTABILITAS KINERJA KEUANGAN SATUAN KERJA PERANGKAT DAERAH KABUPATEN KARANGANYAR - Suprihatmi Sri Wardiningsih, Ria Darmayanti, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2017)
The study aims to analyze the influence of budget participation,budgettargetclarity, accounting control, reporting system, decentralisation,functional supervision and organisation culture to ward the localgovermentsfinancial performanceaccountability of Karanganyar.Testinghypothesis in this research use the regressionanalysis with ttest, Ftest anddeterminationcoeficient (R2). The population in this study is the structuralemployees of regional work unit in Karanganyar. The sampling method ismultistage sampling. The study contains 22 regional work units as a sample.The result of this research are budget participation is not influencing thefinancial performance accountability, budget targets clarity is givingsignificant influence to the financial performance accountability,theaccounting control is giving significant influence to the financial performanceaccountability, the reporting system is not influencing the financialperformance accountability, desentralisation is not influencing the financialperformance accountability, functional supervisionis giving significantinfluence to the financial performance accountability and organisation cultureis giving significant influence to the financial performance accountability.Keywords: financial performance accountability, budget participation,budget target clarity, accounting control, reporting system,decentralisation, functional supervision, organisation culture